2020
DOI: 10.21203/rs.3.rs-46772/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The miR-19b-3p/MAP2K3/STAT3 Feedback Loop Regulates Cell Proliferation and Invasion in Esophageal Squamous Cell Carcinoma

Abstract: Background Esophageal squamous cell carcinoma (ESCC) remains one of the most refractory malignancies worldwide. MAP2K3 has been reported to play an important role in tumor progression. However, whether MAP2K3 also affects ESCC remains to be determined. Method We used a CRISPR/Cas9 kinome screen to identify the genes related to ESCC cell survival. The MAP2K3 expression was detected in ESCC tissues by immunohistochemistry and westernblot. The function of MAP2K3 in ESCC was investigated using colony formation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The function of MicroRNAs is to bind to target gene mRNA, causing mRNA degradation on one hand and inhibiting protein translation on the other, thereby regulating the expression of target genes. Research has confirmed the presence of Open Journal of Stomatology various abnormally expressed MicroRNAs in tongue squamous cell carcinoma tissue, which plays important regulatory roles in its proliferation, differentiation, growth, apoptosis, invasion, and metastasis [2]. This article provides a review of the research status of MicroRNAs in squamous cell carcinoma of the tongue.…”
Section: Introductionmentioning
confidence: 80%
“…The function of MicroRNAs is to bind to target gene mRNA, causing mRNA degradation on one hand and inhibiting protein translation on the other, thereby regulating the expression of target genes. Research has confirmed the presence of Open Journal of Stomatology various abnormally expressed MicroRNAs in tongue squamous cell carcinoma tissue, which plays important regulatory roles in its proliferation, differentiation, growth, apoptosis, invasion, and metastasis [2]. This article provides a review of the research status of MicroRNAs in squamous cell carcinoma of the tongue.…”
Section: Introductionmentioning
confidence: 80%